2010
DOI: 10.1002/cpp.672
|View full text |Cite
|
Sign up to set email alerts
|

Relating therapy for people who hear voices: perspectives from clients, family members, referrers and therapists

Abstract: Current psychological models of voice hearing emphasise the personal meaning that individuals attribute to the voice hearing experience. Recent developments in theory and research have highlighted the importance of the relationship between the hearer and the voice. This study aims to contribute to this area of research, by exploring the experience and usefulness of a new form of 'Relating Therapy' that aims to modify distressing relationships with voices. Semi-structured interviews were conducted with ten part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Specifically, we have explored voice hearing with respect to both the power and proximity aspects of relating and developed RT in order to specifically target these forms of relating. RT aims to re-balance the hearer-voice relationship (without extremes of power or proximal ways of relating) and has been found to be safe, acceptable, and intuitively appealing to therapists and hearers within a previous study [16, 20]. This external pilot RCT will generate a refined study protocol, an indication of recruitment and retention rates, and an estimate of the effect size, in order to inform the sample size calculation for a phase III trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we have explored voice hearing with respect to both the power and proximity aspects of relating and developed RT in order to specifically target these forms of relating. RT aims to re-balance the hearer-voice relationship (without extremes of power or proximal ways of relating) and has been found to be safe, acceptable, and intuitively appealing to therapists and hearers within a previous study [16, 20]. This external pilot RCT will generate a refined study protocol, an indication of recruitment and retention rates, and an estimate of the effect size, in order to inform the sample size calculation for a phase III trial.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the therapists (including the first author) are familiar with the therapy, having previously delivered it within the case series [16, 20]. The three remaining therapists are experienced in the delivery of psychological therapy for psychotic experiences within trials, and will receive training from the first author.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in theory and research have built on this by highlighting the role of the relationship between the voice hearer and the voice (Hayward & Fuller, 2010). Hayward and Fuller (2010) qualitatively examined ‘Relating Therapy’ that aimed to modify distressing relationships with voices.…”
Section: Relationship With Voicesmentioning
confidence: 99%
“…Recent developments in theory and research have built on this by highlighting the role of the relationship between the voice hearer and the voice (Hayward & Fuller, 2010). Hayward and Fuller (2010) qualitatively examined ‘Relating Therapy’ that aimed to modify distressing relationships with voices. The authors found evidence for a model that proposes to bring about positive change by altering relationships with voices (Hayward & Fuller, 2010).…”
Section: Relationship With Voicesmentioning
confidence: 99%